Insights into spinetail devil ray spatial ecology in the Mediterranean Sea through satellite telemetry - Giuseppe Notarbartolo di Sciara; Mohammed Abudaya; Giacomo Milisenda; Simonepietro Canese; Viola Panigada; Jehad Salah; Simone Panigada (Scientific Reports)
Abstract To investigate the seasonal migratory behaviour of spinetail devil rays, Mobula mobular, across the Mediterranean Sea, we used satellite telemetry to track nine individuals between 2016 and 2021. The species is listed as Endangered in the IUCN’s Red List of Threatened Species and appears to be most vulnerable to fishing impacts when gathering in large assemblages. The only known targeted devil ray fishery harvests significant numbers each winter off Gaza. While broadly distributed during summer across the more productive areas of the western and central portions of the Mediterranean, most tracked rays showed an eastward movement towards eastern Levantine waters during the second half of the year. One individual, tagged off Gaza in March 2016, travelled to Spain before swimming back to the Levantine Sea one year later. Our study corroborates the notion that the species undergoes predictable basin-wide migrations across the Mediterranean Sea, favouring the Levantine waters in late winter and early spring, thanks to the subregion’s milder sea surface temperatures in that time of the year compared to the rest of the Mediterranean. Understanding the species’ seasonal movement pattern in the Mediterranean could support the implementation of robust place-based conservation measures, especially in light of unregulated fishing pressure.